Effect of Y2O3-stabilized ZrO2 whiskers on the microstructure, mechanical and wear resistance properties of Al2O3 based ceramic composites. Issue 13 (September 2019) - Fang, Yihang; Chen, Nan; Du, Guoping; Zhang, Mengxian; Zhao, Xianrui; Wu, Jianbo
Abstract: The aim of this study was to improve the mechanical properties of Al2 O3 ceramics by the addition of Y2 O3 -stabilized ZrO2 whiskers (designated as Al2 O3 /YSZW composite) through the flux method and hot-pressing technology. The effect of YSZW content on their microstructure, phase composition and transformability, mechanical properties, and wear resistance was systematically investigated. The Al2 O3 /YSZW composites containing 10 wt% YSZW exhibited the best mechanical performance, including the highest content of YSZW tetragonal phase and transformability as well as the largest values in their relative density (99.5%), hardness (1969 HV), fracture toughness (9.57 MPa m 1/2 ) and flexural strength (855 MPa). The strengthening and toughening of the Al2 O3 /YSZW composites were attributed to the YSZW tetragonal-monoclinic phase transformation as well as the whiskers reinforcing effect. Furthermore, the Al2 O3 /YSZW composites also showed the highest friction and wearing properties.